Influence of Organic Acids on a Non-Conventional Starch from Corypha umbraculifera L. to Improve Its Functionality and Resistant Starch Content - Basheer Aaliya; Kappat Valiyapeediyekkal Sunooj (Biology and Life Sciences Forum, 2021)
Talipot starch isolated from the stem of talipot palm is an underutilized and non-conventional source of starch with a high yield (76%). Resistant starch (RS) possesses varied physiological benefits by acting as a dietary fiber and reduces the risk of many degenerative diseases. The process of starch esterification considerably increases the RS and improves other starch characteristics, such as reducing gelatinization temperature and retrogradation tendency. In the present study, talipot starch was esterified with two organic acids: acetic acid and lactic acid. By introducing the ester group (C=O), the modified starches exhibited a significant decrease (p ≤ 0.05) in amylose content, relative crystallinity, swelling index, gelatinization temperature, and peak viscosity of starch. Lactic acid showed a higher impact on starch depolymerization and RS formation than acetic acid between the organic acids. Esterified talipot starch with a comparatively high yield can be utilized in the preparation of low-calorie foods.